Effect of anaerobic gymnastics exercise on vascular endothelial growth factor in obese boys - Vahid Saleh; Roghayye Afroundeh; Marefat siahkohiyan; Asadollah Asadi (Indonesian Pediatric Society, 2020)
Background Vascular endothelial growth factor (VEGF) is the most important growth factor involved in angiogenesis and appears to be mediated through exercise training, leading to increased blood lactate. Objective To evaluate and compare the effects of anaerobic gymnastics exercise (AGE) on systemic VEGF in obese and normoweight boys. Methods Sixty boys aged 8 to 12 years who enrolled in elementary level of gymnastics participated in this study and were randomly divided into four groups of 15 subjects each: obese AGE, obese control, normoweight AGE, and normoweight control. The control group didn’t have any exercise during the study. The experimental groups performed 45 minutes of AGE 3 times per week for 8 weeks, which included a 10-minute warm-up, 30-minute main exercises, and 5-minute cool down. Body composition characteristics and VEGF levels in saliva were measured before and after 8 weeks of training. Results Significant changes following AGE were found in the obese group in terms of weight (-8.09%; P=0.001), body fat% (BF%) (-12.81; P=0.001), body fat weight (BFW) (-19.38; P=0.001), and lean body weight (LBW) (-3.20; P=0.001). Saliva levels of VEGF increased post-AGE in the obese (+21.64%; P=0.79) and normoweight groups (+28.22; P=0.06), but the differences were not significant. Significant differences in weight, BF%, and BFW were found in between obese AGE group with obese control, normoweight control and normoweight AGE (P˂0.05). Conclusion Circulating VEGF concentrations slightly increase after 8 weeks of AGE in obese and normal-weight groups. Moreover, we demonstrate that weight significantly decreased in obese children after they engaged in AGE training.